Profile of reported cases of exogenous intoxication in a municipality in Ceará from 2017 to 2021 (Research, Society and Development, 2022)
The objective was to describe and analyze the epidemiological profile of cases of compulsory notification of exogenous intoxication in the municipality of Jaguaribe Ceará from 2017 to 2021. This is a cross-sectional, descriptive and quantitative study, carried out through the collection of secondary data of cases of exogenous intoxication reported in the Notifiable Diseases Information System (SINAN) from 2017 to 2021 in the municipality of Jaguaribe, Ceará. Data collection was carried out in the period of July 2022, through access to the portal of the Department of Informatics of the Unified Health System (DATASUS). The data were organized and tabulated with the help of Microsoft Excel (2019) software, and were later analyzed using descriptive statistics and discussed in the literature. From the collection and analysis of data, it was possible to identify 215 cases of reports of exogenous intoxication in the municipality under study. Of these, notifications related to females (60.5%), of mixed race (95%), aged between 20 and 39 years (44.65%), with unknown/white education (61.7%), with medications as the main toxic agent (72.7%), the predominant circumstance being the suicide attempt (44%), single-acute exposure (58.6%) and evolution with cure without sequelae (93.4%). Therefore, it appears that the description of the epidemiological profile of a disease is of paramount importance to support the actions of prevention, promotion and recovery of the health of populations, as well as the formulation of public health policies aiming to reduce the occurrence of cases of intoxication exogenous.